(3cJGH aj EHOGd GdCOhjIs - (3CHh GdYHGS CMeO Hf CHj GdaVd CSYO Hf LdhGf GdWHjH, GHf LdhGfs
(3ChdgG (B:s
(3bGd eG SQLhjg gPg COhjI QDSGA GdCWHGA hYdeGFge ef GdQhe hGdgfO hGdaQS ai EHOGd GdCOhjI s
(3BNQgG (B:s
(3hjfaY ddPi dOYJg GdYbQH Ch HYV OhGH GdCQV HOd eQGQI GdfeQ Je cJGH eG SQMhjg ai EHOGd GdCOhjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs